Stories in management education: Relevance, insights, and perspectives - Rocha, Camilla Netto; Davel, Eduardo (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This study aims to integrate and consolidate academic knowledge about stories in management education. This research is based on a systematic review of national and international academic production. The analysis of identified research resulted in three central categories to explain the field: relevance (communication, engagement, creativity, politics, change, moral, and emotion), knowledge (typologies of stories, management practices, and teaching strategies and learning), and perspectives (storytelling and story writing). By elaborating a structured view of stories in management education, the results of this research contribute to structure, to stimulate, and to guide future research.